The properties of vacancies in solid ⁴He as studied by pressure measurements - Remeijer, P.; Steel, S.C.; Jochemsen, R.; Frossati, G.; Goodkind, J.M. (Физика низких температур, 1997)
The temperature dependence of the pressure at a constant volume in solid ⁴He in the low-density hcp phase has been measured. The measurements are analyzed in terms of a localized vacancy model and the free Bose gas model of vacancies in solid helium. The results agree better with the free Bose gas model. On the basis of this model the effective mass of the vacancies was determined to be 3–5 times the bare mass of a ⁴He atom, which corresponds to a bandwidth of 1.3–2.1 K.